STUDI PIROLISIS MIKROALGA HIJAU (Spirulina platensis) TERHADAP KONSENTRASI PRODUK TURUNAN LIPID - Sahirah, Nabilah Sinar; Subagyono, RR Dirgarini Julia Nurlianti; Gunawan, Rahmat (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Pyrolysis study of Spirulina platensis using Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) instrument has been conducted. In the pyrolysis products identified on the pyrogram, the chemical composition of lipid-derived products was 55.70%. These lipid-derived compounds are hexadecanoic acid (31.05%), oleic acid (6.06%), and octadecanoic acid (3.68%). Keywords: Spirulina platensis, pyrolysis, Py/GC-MS